Descartes' temporal dualism - Waller, Rebecca Lloyd (Lexington Books, 2014)
Rebecca Lloyd Waller defends a temporal dualist interpretation of Descartes' account of time to directly engage and address common interpretive puzzles. Descartes' Temporal Dualism offers a significant contribution to the understanding of an important, but frequently neglected component of Descartes' ontology.